The relationship between family support and self-efficacy in preoperative breast cancer patients: Implications for healthcare practices - Wulandari , Wiwin Kiky; Astuti, Titi; Udani, Giri (Majalah Kesehatan Indonesia, 2024)
Preoperative carcinoma mammae patients frequently experience diminished self-efficacy, which can impede their ability to cope with medical procedures and affect recovery outcomes. Family support is considered a crucial factor in enhancing self-efficacy, offering emotional, informational, and instrumental assistance that strengthens patients’ confidence. This study aims to explore the relationship between family support and self-efficacy in preoperative breast cancer patients at Abdul Moeloek Hospital, Lampung Province, in 2023. Utilizing a cross-sectional design, 78 respondents were selected through non-probability sampling. Family support was measured using a validated family support questionnaire, while self-efficacy was assessed through the Strategies Used by People to Promote Health (SUPPH) questionnaire. The results revealed that 85.9% of patients reported high levels of family support, and 88.5% exhibited strong self-efficacy. Statistical analysis, using the Chi-Square test, indicated a significant relationship between family support and self-efficacy (p = 0.003), reinforcing the theoretical framework of Bandura’s self-efficacy model, which posits that social support enhances individuals' confidence in overcoming challenges. The findings suggest that integrating structured family support programs into preoperative care can improve self-efficacy, ultimately leading to better patient outcomes. This research contributes to the understanding of psychosocial factors in cancer care, emphasizing the need for educational interventions targeting families to optimize patient recovery.